Management of Privacy and Social Identity of Indonesian Islamic Da'wah Institute (LDII) Congregations in Interacting Communication with the Community - Rijalud Dawah; Totok Wahyu Abadi (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to analyze and explain the management of privacy, social identity and communication interactions. The respondents of this study were 100 residents in the Porong and Gedangan sub-districts. The sampling technique in this study used simple random sampling. Primary data was obtained from the distribution of questionnaires according to the problem formulation and research objectives. The data analysis technique used is descriptive statistics. The results showed that privacy management has an effect on communication interactions in Porong and Gedangan sub-districts, which are in the good/high category (78.30%). This means that the privacy management of LDII congregations in Porong and Gedangan sub-districts in interacting communication is still very influential on the surrounding community. What makes the creation of distance between individuals and groups, is caused by the decision to close or open information, as well as the selection of other individuals in interacting communication. In addition to privacy management, social identity is also included in the good/high category (67.54%). this means, social identity has an effect on communication interactions in the Porong and Gedangan sub-districts which are manifested in everyday life.